INTERVIEW WITH ANDREJ KRANJC - Nataša Ravbar (Acta Carsologica, 2014)
Andrej Kranjc is a world-recognized karstologist and speleologist for his achievements in karst geomorphology, hydrology, cave research, karst terminology and history of karst science. In 2013 he celebrated his 70th anniversary. As his student and colleague I took this opportunity to present some highlights of his life and work. Despite being retired already since 2010, he is currently a Vice-President of the Slovenian Academy of Sciences and Arts. During our relaxing and amusing conversation in his office over a cup of coffee the present interview arose.